ITEM ANALYSIS OF MULTIPLE-CHOICE QUESTIONS: AN ASSESSMENT ON ENGLISH SUMMATIVE TEST - Rame , Gracela; Hoinbala, Festif Rudolf (English Education Study Program - Artha Wacana Christian University, 2024)
This study aimed to analyze the test items of multiple choice questions on an English summative test. It examines the quality of the teacher-made test in terms of difficulty level, discrimination power, and the effectiveness of distractors. A descriptive method is applied to describe and analyze the data. The instrument for the data collection is a documentary with a document analysis technique in examining the data. The research finding shows that the test has low reliability. Regarding difficulty level, the majority of items (82,5%) are easy, 5 % desirable and 12,5% difficult. Only 7,5 % of the items were categorized as good discrimination power, while 72% were at a poor level and 20% were at a satisfactory level. Furthermore, only 3 % of the questions showed that the distractors worked effectively. It is concluded that the test needed to be revised, and test makers’ comprehension of the quality of the test is needed to determine the quality of a reasonable and appropriate language assessment.